2010
DOI: 10.1007/s00431-010-1252-1
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal staphylococcal scalded skin syndrome: clinical and outbreak containment review

Abstract: Staphylococcal scalded skin syndrome (SSSS) is a toxin-mediated exfoliating skin condition predominated by desquamation and blistering. Neonatal outbreaks have already been reported; however, our outbreak highlights the potential for SSSS following neonatal health promotion measures such as intra-muscular vitamin K administration and metabolic screening (heel prick) as well as effective case containment measures and the value of staff screening. Between February and June 2007, five confirmed cases of neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 22 publications
0
10
1
3
Order By: Relevance
“…La incidencia de esta enfermedad es mayor en recién nacidos, en quienes se llamó pénfigo neonatorum de Ritter, y en menores de cinco años, por disminución en la depuración de las toxinas, falta de anticuerpos antitoxina o ambas cosas. Esta entidad rara vez afecta los adultos 3,4,12,17 . El foco más frecuente son las infecciones leves de las vías respiratorias superiores y, con menor frecuencia, de las conjuntivas, la región perioral, el ombligo, el periné y el sistema urinario.…”
Section: Síndrome De Piel Escaldada Estafilocócicaunclassified
“…La incidencia de esta enfermedad es mayor en recién nacidos, en quienes se llamó pénfigo neonatorum de Ritter, y en menores de cinco años, por disminución en la depuración de las toxinas, falta de anticuerpos antitoxina o ambas cosas. Esta entidad rara vez afecta los adultos 3,4,12,17 . El foco más frecuente son las infecciones leves de las vías respiratorias superiores y, con menor frecuencia, de las conjuntivas, la región perioral, el ombligo, el periné y el sistema urinario.…”
Section: Síndrome De Piel Escaldada Estafilocócicaunclassified
“…These toxins induce epidermal blistering through the cleavage of the cell-cell adhesion molecule desmoglein-1, which is only expressed by keratinocytes in the granular cell layer, leading to a spectrum of illnesses ranging from mild localized blistering to extensive generalized lesions [2, 5]. ETs producing S. aureus strains have been associated with specific genetic backgrounds, on the basis of their phage types, accessory gene regulator ( agr ) groups and macrorestriction profiles [3–10]. …”
Section: Introductionmentioning
confidence: 99%
“…12 Neonates are also exposed to the risk of acquiring infections caused by Staphylococcus aureus, which colonizes both mothers and staff in the hospital environment, 13,14 considering that one third of the immunocompetent population carries this microorganism. 6 The resistance presented by methicillin-resistant Staphylococcus aureus extends to all β-lactam antibiotics and therefore this is an etiological agent of utmost importance, with regard to both nosocomial infections (hospital-acquired methicillin-resistant…”
Section: Staphylococcus Aureus Is Characterized As a Severe Infectionmentioning
confidence: 99%
“…9 It has been suggested that the action of these toxins is due to their ability to cleave: thus, a protease that targets desmoglein desmosomal adhesion molecule-1 10 leads to loss of cell-to-cell contact in the epidermis,bubbles that are fragile and burst easily, which leaves this area of skin wet and unprotected, such that development of this syndrome is favored. 6 In neonates, staphylococcal scalded skin syndrome produces strains that colonize sites such as the nose and umbilical cord. 12 Neonates are also exposed to the risk of acquiring infections caused by Staphylococcus aureus, which colonizes both mothers and staff in the hospital environment, 13,14 considering that one third of the immunocompetent population carries this microorganism.…”
Section: Staphylococcus Aureus Is Characterized As a Severe Infectionmentioning
confidence: 99%